Stabilization of an elusive tautomer by metal coordination. Issue 7 (23rd June 2021) - Parisi, Emmanuele; Centore, Roberto
Abstract : With reference to a [1, 2, 4]triazolo[3, 2‐ c ][1, 2, 4]triazole ligand, for which the 3 H ‐tautomer has an energy only 1.4 kcal mol −1 greater than the most stable 2 H ‐tautomer, we show that metal complexation is a successful and reliable way for stabilizing the higher‐energy elusive tautomer. Abstract : The solid‐state isolation of the different tautomers of a chemical compound can be a challenging problem. In many cases, tautomers with an energy very close to the most stable one cannot be isolated (elusive tautomers). In this article, with reference to the 4‐methyl‐7‐(pyrazin‐2‐yl)‐2 H ‐[1, 2, 4]triazolo[3, 2‐ c ][1, 2, 4]triazole ligand, for which the elusive 3 H ‐tautomer has an energy only 1.4 kcal mol −1 greater than the most stable 2 H form, we show that metal complexation is a successful and reliable way for stabilizing the elusive tautomer. We have prepared two complexes of the neutral ligand with CuBr2 and ZnBr2, namely, aquabromidobis[4‐methyl‐7‐(pyrazin‐2‐yl)‐3 H ‐[1, 2, 4]triazolo[3, 2‐ c ][1, 2, 4]triazole]copper(II) bromide trihydrate, [CuBr(C8 H7 N7 )2 (H2 O)]Br·3H2 O, and dibromido[4‐methyl‐7‐(pyrazin‐2‐yl)‐2 H ‐[1, 2, 4]triazolo[3, 2‐ c ][1, 2, 4]triazole][4‐methyl‐7‐(pyrazin‐2‐yl)‐3 H ‐[1, 2, 4]triazolo[3, 2‐ c ][1, 2, 4]triazole]zinc(II) monohydrate, [ZnBr2 (C8 H7 N7 )2 ]·H2 O. The X‐ray analysis shows that, in both cases, the elusive 3 H ‐tautomer is present. The results of the crystallographic analysis of the two complexes reflect the different coordination preferences of Cu II and Zn II . The copper(II) complex is homotautomeric as it only contains the elusive 3 H ‐tautomer of the ligand. The complex can be described as octahedral with tetragonal distortion. Two 3 H ‐triazolotriazole ligands are bis‐chelated in the equatorial plane, while a water molecule and a bromide ion in elongated axial positions complete the coordination environment. The zinc(II) complex, on the other hand, is heterotautomeric and contains two bromide ions and two monodentate ligand molecules, one in the 2 H ‐tautomeric form and the other in the 3 H ‐tautomeric form, both coordinated to the metal in tetrahedral geometry. The observation of mixed‐tautomer complexes is unprecedented for neutral ligands. The analysis of the X‐ray molecular structures of the two complexes allows the deduction of possible rules for a rational design of mixed‐tautomer complexes.